ANALISIS KESULITAN SISWA SMP NEGERI 3 PLERET PADA MATERI ARITMATIKA SOSIAL - Maratu Shalikhah (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Social arithmetic material is the focus of this research. Researchers want to find out more about student understanding related to social arithmetic material. In addition, social arithmetic materials require various prerequisite materials that must be mastered by students. The main problem examined in this study is the student's mistake in solving social arithmetic material. This study aims to determine the forms of errors made by students in solving problems related to social arithmetic, the causes, and provide solutions to the errors that have been identified. The subjects in this study were eighth grade students of SMP Negeri 3 Pleret. Student error data obtained from written test results. Student answers are incorrectly identified into the types and forms of errors. After that, several students were selected to be interviewed. This research uses a qualitative approach and the type of research is descriptive. From the results of data analysis it can be concluded that students experience: (1) difficulty in performing the problem solving algorithm; (2) difficulties in understanding the concept of profit or loss if it is associated with the purchase price and selling price; (3) difficulties in understanding the concept of discount. Alternative solutions to overcoming these difficulties are: (1) Teachers need to get used to and emphasize to students so that in working on problems always accompanied by clear steps; (2) Apply themethod Role Playing by utilizing the school canteen.